2021
DOI: 10.36278/jeaht.24.2.62
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Regional Source Contribiution of PM2.5 in the Gwangyang Bay Area

Abstract: Fine particulate matter (PM-2.5) samples were collected over 15 months in the Yeosu and Gwangyang areas from March, 2019 to June 2020. Samples were analyzed for organic carbon, elemental carbon, water-soluble ionic compounds, and trace elements. Source apportionment model (Positive Matrix Factorization) was applied to the data understand monthly and seasonal contributing sources of PM-2.5. Nine source categories with reasonably stable profiles were identified in the Yeosu area such as secondary sulfate (38%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The post-hoc test revealed that the concentration of V was significantly different at D2 compared to all other sites and that the concentration of Mn was significantly different at D1 compared to all other sites. V is generated from the combustion of petroleum fuel [ 26 ], while Mn is released from steel and non-ferrous metal-related facilities [ 27 ]. Hence, our results may be attributed to the fact that Asan national industrial complex, which houses many steel and petrochemical plants, and the Godae·Bugok districts are in the vicinities of D1 and D2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The post-hoc test revealed that the concentration of V was significantly different at D2 compared to all other sites and that the concentration of Mn was significantly different at D1 compared to all other sites. V is generated from the combustion of petroleum fuel [ 26 ], while Mn is released from steel and non-ferrous metal-related facilities [ 27 ]. Hence, our results may be attributed to the fact that Asan national industrial complex, which houses many steel and petrochemical plants, and the Godae·Bugok districts are in the vicinities of D1 and D2.…”
Section: Resultsmentioning
confidence: 99%
“…In Dangjin, Cu was highest in D4; D4 is near the Seokmun national industrial complex, which houses many steel and machinery plants that could have contributed to the results [ 14 ]. Meanwhile, Mn, Cu, and As have been reported to be generated by coal combustion [ 27 ]. Particularly, As is a major metabolite of bituminous coal combustion, and As, Cu, and Fe have also been reported to be released from iron smelting furnaces [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2007) stated that Ag NPs cause DNA damage in Leydig cells, which results in cell death. [ 118 ] Krishnamoorthy et al. (2007) that the aqueous extract of the plant ( Terminalia chebula ) for 45 days causes morphological changes in the testis tissue of mice.…”
Section: Discussionmentioning
confidence: 99%
“…[117] Park et al (2007) stated that Ag NPs cause DNA damage in Leydig cells, which results in cell death. [118] Krishnamoorthy et al…”
Section: Lung Histological Damagementioning
confidence: 99%